Risk factors for disease progression in idiopathic pulmonary fibrosis. Issue 1 (14th October 2019) - Raghu, Ganesh; Ley, Brett; Brown, Kevin K; Cottin, Vincent; Gibson, Kevin F; Kaner, Robert J; Lederer, David J; Noble, Paul W; Song, Jin Woo; Wells, Athol U; Whelan, Timothy P; Lynch, David A; et al.
Abstract : In this retrospective study of a randomised trial of simtuzumab in idiopathic pulmonary fibrosis (IPF), prodromal decline in forced vital capacity (FVC) was significantly associated with increased risk of mortality, respiratory and all-cause hospitalisations, and categorical disease progression. Predictive modelling of progression-free survival event risk was used to assess the effect of population enrichment for patients at risk of rapid progression of IPF; C-index values were 0.64 (death), 0.69 (disease progression), and 0.72 (adjudicated respiratory hospitalisation) and 0.76 (all-cause hospitalisation). Predictive modelling may be a useful tool for improving efficiency of clinical trials with categorical end points.